The Rapid Effect of Bisphenol-A on Long-Term Potentiation in Hippocampus Involves Estrogen Receptors and ERK Activation - Xiaowei Chen; Yu Wang; Fang Xu; Xiaofei Wei; Junfang Zhang; Chuang Wang; Hua Wei; Shujun Xu; Peiyun Yan; Wenhua Zhou; Istvan Mody; Xiaohong Xu; et al. (Neural Plasticity)
Bisphenol-A (BPA), a widely used synthetic compound in plastics, disrupts endocrine function and interferes with physiological actions of endogenous gonadal hormones. Chronic effects of BPA on reproductive function, learning and memory, brain structure, and social behavior have been intensively investigated. However, less is known about the influence of BPA on long-term potentiation (LTP), one of the major cellular mechanisms that underlie learning and memory. In the present study, for the first time we investigated the effect of different doses of BPA on hippocampal LTP in rat brain slices. We found a biphasic effect of BPA on LTP in the dentate gyrus: exposure to BPA at a low dose (100 nM) enhanced LTP and exposure to BPA at a high dose (1000 nM) inhibited LTP compared with vehicle controls. The rapid facilitatory effect of low-dose BPA on hippocampal LTP required membrane-associated estrogen receptor (ER) and involved activation of the extracellular signal-regulated kinase (ERK) signaling pathway. Coadministration of 17β-estradiol (E2, the primary estrogen hormone) and BPA (100 nM) abolished both the BPA-induced enhancement of LTP and the E2-induced enhancement of baseline fEPSP, suggesting a complex interaction between BPA- and E2-mediated signaling pathways. Our investigation implies that even nanomolar levels of endocrine disrupters (e.g., BPA) can induce significant effects on hippocampal LTP.